رؤية نصر حامد أبو زيد لعِلْمَيْ المكي والمدني والناسخ والمنسوخ. -دراسة تحليلية نقدية- - خنوفه, صلاح الدين (University of eloued جامعة الوادي, 2021)
يَخْلُصُ هذا البحث إلى التركيز على دراسة عِلْمَيْ من علوم القرآن ( علم المكي والمدني، علم الناسخ والمنسوخ)من وجهة نظر نصر حامد أبو زيد، حيث قمت بالترجمة لأبو زيد، ثم تطرقت لنظرته حول علم المكي والمدني، من معايير للتمييز بين المكي والمدني، ومنهج التلفيق بين الروايات، وفرض تكرر النزول ، والفصل بين النص والحكم، وبعدها حوّلت النظر إلى علم الناسخ والمنسوخ وما نظّر أبو زيد. حوله كمفهوم النسخ، ووظيفته، وأنماطه، والانفصال بين الحكم والتلاوة، والنسخ وأزلية النص، فعرضت آراءه حول العِلْمَين وناقشته فيهما.This resaerch concludes to focus on studing two of( the science of naskh and mansukh) from the point of view of Nasr Hamed Abi Zaid, Where I Write about Abi Zaid biography and then I mentioed his point of view about Makki and Madani science how was his criteria for discrimination between Makki and Madani Talfiq methodology between riwayat and the imposition of rewarding and separiting the text and the judgement. After that turned to the science of nsaskh and munskh Abu Zaid definition about it its function and types and separation between judgement and tilawa Naskh and the orientation of the text. I give his points of views about the two sciences and discussed its views.
علوم قرآن
Keywords: الحداثة-الاستشراق- نصر حامد أبو زيد- الناسخ والمنسوخ- المكي والمدني.; El Hadatha- Istishraq- Nasr Hamed abu Zaid- Naskh and Munsukh- Makki and Madani